Rheumatoid Arthritis: Pattern and Prevalence of Extra-Articular Manifestations - A Prospective Study - Haidar, MS; Razzak, MA; Yasin, MM (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i2.16353 JAFMC Vol.8(2) 2012 pp.39-46